An intra-abdominal desmoid tumor - Petró, Mátyás (Acta Radiol Open, 2021)
Desmoid tumor is a very rare neoplasm which develops from fibroblasts. These tumors do not have the ability to metastasize, but they can cause significant morbidity and mortality by local invasion and they are prone to local recurrence. We present a case of an aggressive fibromatosis in a 28-year-old male patient with no previous medical history. The tumor was in the retroperitoneum and eventually caused perforation of the coecum. During the operation, no metastasis was found; however, local lymphadenopathy was seen. After the surgical resection, no adjuvant therapy (radio or chemotherapy) was given to the patient and on follow-up (after three years), no recurrence was observed.